Model Kredibilitas Bühlmann dengan Frekuensi Klaim Berdistribusi Binomial Negatif-Lindley - Ikhsan Maulidi; Vina Apriliani (Limits: Journal of Mathematics and Its Applications, 2021)
In this article, we develop a parametric Bühlmann credibility model with the frequency of claims that are assumed following the Negative Binomial- Lindley distribution. The Estimator of the quantities in the Bühlmann model have provided for this distribution using methods commonly used in the greatest accuracy credibility. The premium estimation that resulted in this model is a linear combination of the past claims which gives a minimum error square. The momen function of the Binomial-Lindley distribution is very helpful to determine these Bühlmann’s quantities. Application simulations of this model are also given for simple data claims along with the algorithm. However, it gives an appreciable credibility factor value, this model requires many past claims to get a good premium estimation.